PENDAMPINGAN CALON MAHASISWA KARTU INDONESIA PINTAR BAGI PENINGKATAN PENDIDIKAN MASYARAKAT KETERBATASAN EKONOMI - Dede Suhendi; Jajam Muhamad Jamhur (ICON Publisher, 2024)
Higher Education plays a role in creating superior Human Resources, through participation in government programs that aim to provide education scholarships at the Higher Education Level as prospective students, the right method is needed to determine the right students in accordance with the allocation for people who are included in the economically limited group. The Selection Method selectively involves the New Student Admission Team and the KIP Student Prospective Assistance Team is expected to make it easier to determine students who are eligible for this scholarship facility. Determining the ranking of suitability in the assessment of KIP scholarships involves several systematic steps using the Simple Additive Weighting (SAW) method consisting of data collection, determining the weight of the criteria, calculating the value based on the criteria, compiling based on the ranking so that the assessment information can be based on selection.